Algebraic Equivalence and Proof

Algebraic Equivalence

Algebraic equivalence is the idea that two algebraic expressions or equations represent the same mathematical relationship or have the same solution set.

We can transform equivalent expressions into each other through algebraic operations, such as addition, subtraction, multiplication, division, substitution, and factoring.

Understanding algebraic equivalence is important for simplifying expressions and solving equations, as it helps identify different representations of the same mathematical relationship.

Let’s look at some examples:

Example: Algebraic Equivalence in Expressions

Consider the expressions 3(x - 2) and 3x - 6. These expressions are algebraically equivalent because we can use the distributive property to transform one expression into the other:

3(x - 2) = 3x - 3 \times 2

= 3x - 6

Therefore, the expressions 3(x - 2) and 3x - 6 represent the same mathematical relationship.

Example: Algebraic Equivalence in Equations

Consider the equations 2x + 4 = 8 and x + 2 = 4. We can show that these equations are equivalent by dividing both sides of the first equation by 2:

\frac{(2x + 4)}{2} = \frac{8}{2}

x+ 2 = 4

Both equations have the same solution set, x = 2, and represent the same mathematical relationship.

Mathematical Proof

Mathematical proof is a logical argument that establishes the truth of a mathematical statement or theorem. Proofs are important in mathematics because they ensure that results are valid, consistent and reliable.

In algebra, there are several proof techniques you should get familiar with, including direct proof and proof by contradiction.

  • Direct proof involves a series of logical steps that follow from given assumptions or axioms to reach a desired conclusion.
  • Proof by contradiction assumes the opposite of the statement to be proven and demonstrates that this assumption leads to a logical contradiction. This establishes the truth of the original statement.

Let’s look at some examples:

Example: Direct Proof

Prove that the expressions (a + b)^2 and a^2 + 2ab + b^2 are algebraically equivalent for all real numbers a and b.

Expand the expression (a + b)^2(a + b)^2 using the distributive property (also known as the FOIL method):

(a + b)^2 = (a + b)(a + b)(a + b)^2 = (a + b)(a + b)

= a(a + b) + b(a + b)= a(a + b) + b(a + b)

= a^2 + ab + ab + b^2= a^2 + ab + ab + b^2

= a^2 + 2ab + b^2= a^2 + 2ab + b^2

Since the expressions (a + b)^2(a + b)^2 and a^2 + 2ab + b^2a^2 + 2ab + b^2 can be transformed into each other through valid algebraic operations, we have demonstrated that they are algebraically equivalent for all real numbers a and b.

Example: Proof by Contradiction

Prove that \sqrt{2} is irrational.

Assume the opposite, that \sqrt{2}\sqrt{2} is rational. If \sqrt{2}\sqrt{2} is rational, it can be expressed as a fraction \frac{a}{b}\frac{a}{b}, where a and b are integers with no common factors other than 1. So, we have:

\sqrt2 = \frac{a}{b}\sqrt2 = \frac{a}{b}

Squaring both sides of the equation, we get:

2 = \frac{a^2}{b^2}2 = \frac{a^2}{b^2}

Rearranging, we find:

a^2 = 2b^2a^2 = 2b^2

This implies that a^2a^2 is an even number (since it is divisible by 2). If a^2a^2 is even, then aa must also be even. Let a = 2ka = 2k, where k is an integer. Substituting this into the equation, we get:

(2k)^2 = 2b^2(2k)^2 = 2b^2

4k^2 = 2b^24k^2 = 2b^2

Dividing both sides by 2, we have:

2k^2 = b^22k^2 = b^2

This implies that b^2b^2 is also even, which means that b is even as well. However, this contradicts our initial assumption that aa and bb have no common factors other than 1, since both a and b are divisible by 2. Therefore, our assumption that \sqrt{2}\sqrt{2} is rational must be false, and \sqrt{2}\sqrt{2} must be irrational.

Understanding Odd and Even Numbers

In mathematics, numbers can be classified as even or odd based on their divisibility by 2. An even number is divisible by 2, while an odd number is not.

Even numbers can be represented as 2x, where x is any natural number, and odd numbers can be represented as 2x + 1, where x is any natural number.

Let’s look at the rules for the addition and multiplication of even and odd Numbers:

  • Even + Even = Even
  • Even × Even = Even
  • Odd + Odd = Even
  • Odd × Odd = Odd
  • Even + Odd = Odd
  • Even × Odd = Even

Ok, now let’s look at the proof for Even + Even = Even

To demonstrate the rule that the sum of two even numbers is also even, consider two even numbers 2a and 2b, where a and b are natural numbers:

2a + 2b = 2(a + b)

As we can factor out a 2 from the sum of 2a and 2b, it confirms that the result is also even.

Similar proofs can be constructed for the other rules, using the representations of even and odd numbers as 2x and 2x + 1, respectively.

You’ve used 10 of your 10 free revision notes for the month

Sign up to get unlimited access to revision notes, quizzes, audio lessons and more

Sign up